2022
DOI: 10.1002/anie.202212861
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding 30 % External Quantum Efficiency in Non‐doped OLEDs Utilizing Solution Processable TADF Emitters with High Horizontal Dipole Orientation via Anchoring Strategy

Abstract: Strategies to enhance the ratio of the molecular horizontal emitting dipole orientation (Θ k ) for thermally activated delayed fluorescence (TADF) emitters have unlocked the full potential of efficiencies for the evaporated devices, which, however, remain elusive for the solution-processed ones. Here, a strategic molecular design for solution processable TADF emitters featuring high Θ k s is proposed by attaching flexible chains ended with bipolar 9,9'-spirobi[fluorene] subunits as anchoring groups onto TADF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 96 publications
0
24
0
1
Order By: Relevance
“…showed that by attaching flexible chains with terminal 9,9′‐spirobi[fluorene] (HSF) units to a known TADF emitter core can contribute to a more horizontal orientation of the TDM by increasing the effective planarity of the compound [19d] . The TDM of 5CzBN‐HSF is 72 % horizontally oriented in the neat film, while the referencing compound, 5CzBN‐Hex (without HSF units), possesses an isotropically orientated TDM [19d] . These studies opened a new horizon for the use of liquid crystalline materials in OLEDs, especially in terms of the tuning of the film morphology and molecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…showed that by attaching flexible chains with terminal 9,9′‐spirobi[fluorene] (HSF) units to a known TADF emitter core can contribute to a more horizontal orientation of the TDM by increasing the effective planarity of the compound [19d] . The TDM of 5CzBN‐HSF is 72 % horizontally oriented in the neat film, while the referencing compound, 5CzBN‐Hex (without HSF units), possesses an isotropically orientated TDM [19d] . These studies opened a new horizon for the use of liquid crystalline materials in OLEDs, especially in terms of the tuning of the film morphology and molecular orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Another point needed to think about is that, in contrast to vacuum evaporation, solution process is expected to be a promising technology for large‐area commercial production, which puts forward higher requirements for the solubility and film‐forming ability of the corresponding materials. [ 22–26 ] Hence, how to design suitable solution‐processed TADF regioisomers and dissect the inner structure‐properties relationship is more urgent for enriching solution‐processed OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly analyzing the relationship between structure which puts forward higher requirements for the solubility and film-forming ability of the corresponding materials. [22][23][24][25][26] Hence, how to design suitable solution-processed TADF regioisomers and dissect the inner structure-properties relationship is more urgent for enriching solution-processed OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, significant experimental efforts have been made to capitalize on higher EQE of over 30.7% by in-silico design of molecular configurations and device fabrications. 31,32 Nevertheless, the higher performance of TADF-based organic-light emitting devices and an in-depth understanding of material properties based on the features representing the generalized model still need to be improved. Therefore, a design principle with good descriptors is a prerequisite to enhance the modeling of TADF materials for efficiency enhancement.…”
Section: Introductionmentioning
confidence: 99%